Traits of effective leaders in educational institutions - UiTM, MITASA (Kesatuan Kakitangan Akademik UiTM (MITASA), 2025)
However, despite its benefits, TikTok also presents some challenges for learners. One of the main concerns is distraction. Since TikTok is designed mainly for entertainment, learners may find themselves scrolling endlessly through unrelated videos instead of focusing on educational content. Additionally, not all videos provide proper language usage, which may lead to the adoption of incorrect expressions. Therefore, learners must be mindful of the content they watch to ensure they are learning from reliable sources.